Dilema Produktivitas dan Reproduksi: Analisis Konflik Peran dan Strategi Adaptasi Perempuan Pengolah Rajungan di Madura - Anita Kristina; Anita Kristina (Pusat Studi Wanita dan Keluarga UGM, 2026)
This study examines the dilemma of productivity and reproduction faced by female crab processors in coastal Madura, specifically focusing on Kebundadap Village, Sumenep. Employing an interpretive phenomenological methodology, this research delves into the essence of participants' lived experiences through in-depth interviews. Findings reveal that female crab processors experience significant tension due to long working hours, the precarious nature of their work (often seasonal and dependent on raw material availability), and traditional gender expectations regarding household roles. This conflict not only depletes their time and physical energy but also impacts their psychological well-being. They develop diverse adaptation strategies, including meticulous time management, informal labor division with family members, and leveraging community support from fellow workers. The analysis of these findings is enriched by utilizing role conflict theory and social agency theory to understand how individuals navigate social structures and exercise agency when confronting limitations. This research offers a significant contribution to the literature on gender studies and the labour economics, particularly concerning the experiences of women in the informal marine processing sector, and provides an empirical basis for the formulation of more gender-responsive policies aimed at supporting the welfare of female workers.